Дезінформація про українських біженців під час передвиборчої агітації перед парламентськими виборами в Республіці Польща 15 жовтня 2023 року - Тодосійчук, Юрій Іванович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The article explores the role of Ukrainian refugees’ issue in Polish parliamentary election of 15.10.2023. Mostly the author sheds light on the activities of the nationalist-leaning Confederation and its narrative against Ukrainian migrants. The article also exposes disinformation campaigns targeting Ukrainian refugees, analyzing false claims circulated on Telegram channels. Despite attempts to exploit anti-Ukrainian sentiment for political gains, the parliamentary election results underscore the limited success of such rhetoric in Polish society, with mainstream parties dominating and nationalist factions receiving minimal support.